MODOUS OF LAUGHTER IN THE WITH A COMPOSITION-PLOT SYSTEM OF ZAHIDNOOUCRAINSCOI PROSE OF END ХІХ – BEGINNING OF THE ХХ ITEM - Marchuk, G. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article the specific of discourse of satiric prose of end is explored XIX - beginning of the XX item The stylish receptions of humor, satiric hyperbola, fantasy and grotesque are examined, narration form of mystification, facilities of kind of creation in the satiric stories of end XIX – beginning XX centuries, the tendencies of subsequent genre transformations are outlined, three modulus of laughter is determined.